KEJANG DEMAM DAN PENATALAKSANAANNYA - Irdawati, Irdawati (Universitas Muhammadiyah Surakarta, 2009)
Fever stiff is the rise of stiff that happens in increasing of body temperature (the rectal temperature above 380 C) that is caused by a ekstrakranium process. It can cause physical defect, mental defect, behavior disorder, learning disorder, epilepsy even death. Fever stiff is medical emergency that needs immediate assistance. Early diagnosis and appropriate management are needed to avoid serious defect, that is caused by frequent fever stiff. Nursing maintain priority in fever stiff is: prevent/control defect activity, to protect patient from the trauma, maintain breath way, increasing positive self-esteem, giving information to the family about illness process, prognosis and the needs maintain.